2019
DOI: 10.1111/mec.15068
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of ecologically distinct units of marine Bacteroidetes in the Northwestern Mediterranean Sea

Abstract: Bacteroidetes is one of the dominant phyla of ocean bacterioplankton, yet its diversity and population structure is poorly understood. To advance in the delineation of ecologically meaningful units within this group, we constructed near full-length 16S rRNA gene clone libraries from contrasting marine environments in the NW Mediterranean. Based on phylogeny and the associated ecological variables (depth and season), 24 different Bacteroidetes clades were delineated. By considering their relative abundance (fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 91 publications
5
12
0
1
Order By: Relevance
“…The resulting tree indicated that the NAAMES ASVs clustered into three distinct clades, and each of these clades included at least one closely related SAG for genome comparison (Figure 5). The phylogenetic placement of the NAAMES flavobacteria ASVs is consistent with previous research that has indicated that there is a high degree of niche specialization amongst these organisms (Diez-Vives et al, 2019). The SAGs were then queried for B1 synthesis capacity.…”
Section: Stations 1 and 2 Have Contrasting Relationships Between Trcssupporting
confidence: 76%
“…The resulting tree indicated that the NAAMES ASVs clustered into three distinct clades, and each of these clades included at least one closely related SAG for genome comparison (Figure 5). The phylogenetic placement of the NAAMES flavobacteria ASVs is consistent with previous research that has indicated that there is a high degree of niche specialization amongst these organisms (Diez-Vives et al, 2019). The SAGs were then queried for B1 synthesis capacity.…”
Section: Stations 1 and 2 Have Contrasting Relationships Between Trcssupporting
confidence: 76%
“…Among the non-shared Bacteroidetes genera or groups, the NS5 marine group, Polaribacter, Pseudarcicella, and Fluviicola (a typical freshwater genus) characterized water samples, whereas Lutimonas and Maribacter were retrieved in sediments. A number of authors have reported on the dominance of flavobacterial phylotypes responding to phytoplankton blooms, with the succession of particular clades (including Ulvibacter spp., Polaribacter spp., and NS5 marine clades) and the progressive consumption of the algal-derived organic matter [44,45]. In this study, the NS5 marine group was found at very high percentages, also at inner stations, and its co-occurrence with some clades cited above was especially evident at the middle station 9w, suggesting that an algal bloom was present at sampling time.…”
Section: Discussionsupporting
confidence: 52%
“…Bacteroidetes, globally distributed in human gut, coastal ocean, marine sediments and other environments, play key roles in the degradation of high molecular weight carbohydrates ( Cottrell Kirchman, 2000; Fernandez-Gomez et al, 2013; Thomas et al, 2011 ). As such, Bacteroidetes are recognized as one of the dominant phyla of ocean bacterioplankton ( Diez-Vives et al, 2019 ) and are the most important decomposer for algae derived carbohydrates, actively driving the ocean carbon and nutrient cycling ( Kruger et al, 2019; Unfried et al, 2018 ). As compared to studies of Bacteroidetes derived from the shallow ocean, very little research has been done on the deep-sea counterparts, likely due to the difficulties of sampling and cultivation.…”
Section: Discussionmentioning
confidence: 99%